2014
DOI: 10.3758/s13420-014-0143-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of context relevance during extinction learning

Abstract: In two predictive-learning experiments, we investigated the role of the informational value of contexts for the formation of context-specific extinction learning. The contexts were each composed of two elements from two dimensions, A and B. In Phase 1 of each experiment, participants received acquisition training with a target cue Z in context A1B1 (the numbers assign particular values on the context dimensions). In Phase 2, participants were trained with conditional discriminations between two other cues, X a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
1
13
0
1
Order By: Relevance
“…This overall effect was based solely on the performance change in the SWITCH group, who showed renewal only in the SAL session, while the renewal rates in the REN group were not significantly altered by the context manipulation. The higher renewal rates observed in the SAL session complement behavioral studies (Lucke et al, 2013(Lucke et al, , 2014 by demonstrating that not only a relevant context, but also a particularly conspicuous context without specific informational value has the potential to strengthen context-specific learning. The behavioral results also resemble those of a previous study with a between-subjects design, in which the presentation of the context alone also yielded higher renewal rates (Lissek et al, 2016).…”
Section: Enhancing Context Salience Induced More Participants To Showsupporting
confidence: 57%
See 1 more Smart Citation
“…This overall effect was based solely on the performance change in the SWITCH group, who showed renewal only in the SAL session, while the renewal rates in the REN group were not significantly altered by the context manipulation. The higher renewal rates observed in the SAL session complement behavioral studies (Lucke et al, 2013(Lucke et al, , 2014 by demonstrating that not only a relevant context, but also a particularly conspicuous context without specific informational value has the potential to strengthen context-specific learning. The behavioral results also resemble those of a previous study with a between-subjects design, in which the presentation of the context alone also yielded higher renewal rates (Lissek et al, 2016).…”
Section: Enhancing Context Salience Induced More Participants To Showsupporting
confidence: 57%
“…Correspondingly, attention to a context was found to modulate context-specificity of behavior (Uengoer et al, 2018). Relevant contexts received more attention (in terms of gaze duration), which led to more context-specific learning of humans in a behavioral predictive learning task (Lucke et al, 2013(Lucke et al, , 2014. Conceivably, a context attracting attention by its high visibility will appear more salient and also affect context-specific learning.…”
Section: Introductionmentioning
confidence: 93%
“…Despite obvious differences in processing requirements, previous studies highlighted the parallels between context-related extinction learning with and without a fear component: In both, fear (for review see Bouton, 2002, 2004) and non-fear related extinction (Rosas and Callejas-Aguilera, 2006; Rosas et al, 2006; Ungör and Lachnit, 2006; Üngör and Lachnit, 2008; Lucke et al, 2013, 2014), the renewal effect has been demonstrated. Moreover, recent imaging/lesion studies emphasized involvement of similar brain regions in both types of extinction learning, in animals as well as in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Its efficiency was demonstrated in several behavioral as well as fMRI studies, which investigated context-dependent extinction learning (Lissek et al, 2013, 2015a,b). Moreover, this study design has previously been adapted to examine variations in renewal (ABA, ABC, AAB) and their manipulations (e.g., context relevance) (Üngör and Lachnit, 2008; Lucke et al, 2014) as well as the effects of pharmacological modulations on extinction and retrieval (e.g., cortisol, dopamine, noradrenalin) (Hamacher-Dang et al, 2013; Lissek et al, 2015a,b). …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, removal of 'safety signals and behaviors' (such as the presence of other persons, medication, or cell phones) may be another strategy to increase threat expectancies in the short run, but support their violation as the omission of the aversive outcome during extinction training is not associated with the safety signal or behavior (for a critical evaluation see [48,69 && ]). Another target for augmentation results from findings that fear extinction hardly generalizes to different stimuli and contexts, that is, fear likely returns when a different fear stimulus is encountered or if the current context differs from the extinction context [75,76], see also [77]. Different ways of increasing the 'variability' of extinction training may target this crucial issue.…”
Section: Key Pointsmentioning
confidence: 99%